THE GROWTH OF SIX RICE VARIETIES BETWEEN THREE YEARS AGE HEVEA - Tumpal HS Siregar; Sumihar Hutapea; Retna Astuti; Asmah Indrawati; Fachru Yuzairi; Ilham Hidayat (CV. Radja Publika, 2023)
This study aims to achieve two main things simultaneously, namely formulating an intercropping cultivation technique so as to increase the income of Hevea farmers and contribute hevea plantations to independent food supply. The method used in this research is a field research design. Planting Hevea with 1 clone, namely PB 260, combined with 6 rice varieties, namely Impago 7.Rindang I, Rindang 2, Sibundong, Hamparan Perak and MSP 17. with 3 replications. Each variety was planted in 1 x 1m plots, in 3 year old Hevea plantations. The goal to be achieved in this research is to obtain a technology package based on Hevea cultivation to optimize growth and indicate varieties that are resistant to shade. in the long run, this research encourages the importance of finding shade tolerant varieties. On the other hand, the development of this research plot will encourage other intercropping studies, namely Hevea with coffee and cocoa plantations so that in the long term it is profitable for Hevea farmers and adds value to the concept of agricultural agroecology. From a growth perspective, the varieties Rindang 1 and 2 and Hamparan Perak have the potential to be cultivated on Hevea TBMs aged 3 years.